Large Orders in Small Markets: Execution with Endogenous Liquidity Supply - Agostino Capponi; Albert J. Menkveld; Hongzhong Zhang (Tinbergen Institute, 2023)
We model the execution of large uninformed sell orders in the presence of strategic competitive market makers. We solve for the unique symmetric equilibrium of the model in closed-form. Our equilibrium findings provide a rationale for the empirically observed patterns of (i) short orders exhibiting higher intensity of execution and (ii) price pressure potentially subsiding before execution is completed. The model further generates a liquidity surface where the total price impact depends both on the size and duration of the order. Lastly, our analysis demonstrates that large orders unequivocally benefit market makers, while smaller investors stand to benefit only if the order trades with a sufficiently high intensity.
Keywords: G10; 330; Liquidity; market makers; welfare covariance matrices